Stunting dan Faktor Ibu - Aulia, Aulia; Puspitasari, Dian Ika; Huzaimah, Nailiy; Wardita, Yulia; Sandi, Aldi Prawira (Fakultas Ilmu Kesehatan, 2021)
Stunting and Maternal Factors. Stunting is still one of the unresolved priority issues. Maternal factors greatly influence the incidence of stunting in children. This study explains the relationship between stunting and maternal factors, namely education, knowledge of nutrition, parenting patterns, and mother's motivation. This qualitative research is a type of correlational analytic research with the cross-sectional method. The subjects of this study were stunting mothers and toddlers at Dungkek Health Center (n=40), obtained using simple random sampling. Data collection using questionnaires and met lines. Data were analyzed using a contingency correlation test. The results showed a relationship between stunting in children with education, nutritional knowledge, and self-efficacy (p= 0.001; p= 0.033; p= 0.01). Edit was not related to parenting (p = 0.866). Health workers need to pay attention to maternal factors as the target of promotive and preventive activities in stunting cases because maternal factors make an important contribution in the first 1000 days of life, preventing stunting.